Omaveloxolone inhibits IL-1β-induced chondrocyte apoptosis through the Nrf2/ARE and NF-κB signalling pathways in vitro and attenuates osteoarthritis in vivo - Jiang, Zengxin; Qi, Guobin; Lu, Wei; Wang, Hao; Li, Defang; Chen, Weibin; Ding, Lei; Yang, Xiuying; Yuan, Hengfeng; Zeng, Qingmin (Frontiers in Pharmacology, 2022)
determine whether omaveloxolone has a therapeutic effect on OA. Chondrocytes were treated with interleukin (IL)-1β to establish an OA cell model in vitro. Indicators of cell viability, oxidative stress, inflammation, cell apoptosis and extracellular matrix (ECM) degradation were investigated. Proteins related to the Nuclear factor erythroid derived-2-related factor 2 (Nrf2)/ antioxidant response element (ARE) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signalling pathways were assessed using Western blotting. A destabilized medial meniscus surgery-induced OA rat model was used in vivo. Gait analysis, microcomputed tomography analysis, and histopathological and immunohistochemical analyses were performed to determine the therapeutic effect of omaveloxolone on attenuating osteoarthritis in vivo. The results showed that omaveloxolone exerts antioxidative, anti-inflammatory, antiapoptotic and anti-ECM degradation effects via activation of the Nrf2/ARE signalling pathway and inhibition of the NF-κB signalling pathway in chondrocytes in vitro and attenuates OA progression in vivo, suggesting that omaveloxolone may be a potential therapeutic agent for OA.